Synthetic fibrosis distributions for data augmentation in predicting atrial fibrillation ablation outcomes: an in silico study - Zolotarev, Alexander M.; Johnson, Kiane; Mohammad, Yusuf; Alwazzan, Omnia; Slabaugh, Gregory; Roney, Caroline H. (Frontiers in Cardiovascular Medicine, 2025)
IntroductionCardiac fibrosis influences atrial fibrillation (AF) progression and ablation outcomes, with late gadolinium enhancement (LGE) MRI providing a non-invasive tool to measure fibrosis distributions. While deep learning (DL) has shown promise in predicting ablation success, training such pipelines is limited by the availability of real patient data.MethodsIn this study, we generated synthetic fibrosis distributions using a denoising diffusion probabilistic model trained on a collection of 100 real LGE-MRI distributions. We incorporated them into 1,000 bi-atrial meshes derived from a statistical shape model and simulated AF episodes on them before and after various ablation strategies to expand the training dataset for DL-based outcome prediction. Our approach aims to improve the predictive performance of the DL pipeline by enhancing dataset diversity and better-capturing patient variability.ResultsWe showed that the fibrosis distributions generated by the diffusion model closely resemble real LGE-MRI distributions, based on metrics such as mean intensities (1.1±0.2 vs. 1.1±0.3) and average Shannon entropy (0.77±0.06 and 0.81±0.03). AF biophysical simulations can be effectively conducted on bi-atrial meshes incorporating these synthetic distributions. Training the deep learning pipeline on these simulations produces performance metrics comparable to those achieved with real LGE-MRI distributions (ROC-AUC = 0.952 vs. 0.943).ConclusionWe have shown the ability of synthetic fibrosis distributions to be a data augmentation tool for deep learning classification of outcomes of various ablation strategies, which may enable rapid and precise assessment of atrial fibrillation treatment strategies.